Context of use and productive processes in hunter-gatherer and fishing societies from the uttermost tip of South America: a new approach - Alvarez, Myrian Rosa (2012)
Context of use and productive processes in hunter-gatherer and fishing societies from the uttermost tip of South America: a new approach. The attempts to explain tool diversity has been put in archaeological agenda during the ´80. Recently this topic has recovered a renewable impetus fueled by different related to agent-based perspective. Despite the efforts made in use-wear investigation, the most common approaches that deal with tools variability generally do not take account how the functional field affects technological decisions and social dynamic. The scarce level of success of the analytical proposals addressed to unveil form-function relationship accounts for this problem. The aim of this work is to present a method focused primarily on the context of use in which stone tools were employed to explore in a second instance, which are the elements of design associated with a particular task. This method lies on two goals: to deconstruct the common assumption followed by classic perspectives that proposed the existence of a single function for each tool type and to recognize the array of morpho-technical traits that were selected to perform different labour processes. To accomplish this aim we will focus on lithic technology developed by hunter-gatherer and fishing societies who inhabited the uttermost tip of South America since the Middle Holocene.